2008
DOI: 10.1590/s1413-86702008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Anti-Tp47 antibodies in patients with positive serology for syphilis analized by western blot

Abstract: In Brazil, syphilis is still a great problem of public health. Serological test is essential for syphilis diagnosis and the current trend is the use of recombinant antigen in the treponemal tests, due to its confirmed higher sensibility and specificity. The purpose of the present study was to analyze the profile of anti-Tp47 antibodies in patients with positive serology for syphilis. One hundred positive sera samples were analyzed by Western Blot (WB) technique, using the recombinant antigen (rTp47). Ten of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The use of one antigen Tp47 also showed an equivalent diagnostic value to that of combination of three antigens. This was in line with reference suggesting that Tp47 antigens were the most immunogenic and dominant protein, while Tp17 and Tp15 were detected in fewer levels, despite 24 of their equally strong immunogenicity.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The use of one antigen Tp47 also showed an equivalent diagnostic value to that of combination of three antigens. This was in line with reference suggesting that Tp47 antigens were the most immunogenic and dominant protein, while Tp17 and Tp15 were detected in fewer levels, despite 24 of their equally strong immunogenicity.…”
Section: Methodssupporting
confidence: 92%
“…Study by Miranda and Sato suggested that although Tp47 showed activity as a component of major antigens, combination of Tp17, Tp15, and Tp47 antigen was important for syphilis serological 24 tests.…”
Section: Methodsmentioning
confidence: 99%
“…pallidum , and also are the three major immunogens in experimental and natural T . pallidum infection[2324]. During T .…”
Section: Introductionmentioning
confidence: 99%
“…36 It is worth mentioning that Tp47 is the most abundant protein in T. pallidum and has strong immunogenicity. 37 Our study found that Tp47 inhibited macrophage phagocytosis to produce PGE2 by activating the PERK/NF-κB/COX-2 pathway. This conclusion is supported by the ability of the administration of the PGE2 antibody to restore the inhibition of macrophage phagocytosis by Tp47.…”
Section: Discussionmentioning
confidence: 56%